Electoral systems and income inequality: a tale of political equality - Izaskun Zuazu (Empirical Economics, 2021)
The link between democracy and within-country income inequality remains an unresolved quest in the literature of political economy. To look into this debate, I propose exploring the implications of electoral systems, rather than political regimes, on income inequality. I surmise that proportional representation systems should be associated with lower income inequality than majoritarian or mixed systems. Further, I conjecture that the relationship between electoral systems and income inequality hinges on the de facto distribution of real political power, namely political equality. I use data on 85 countries covering the period 1960–2016 and specify models able to capture the persistence and mean reversion of income inequality. The estimates fail to significantly associate democracy with income inequality, and find other political institutions to significantly shape income inequality. The paper finds a robust association between more proportional systems and lower income inequality. However, this association depends on political equality. Changes towards proportional representation systems seem to lower income inequality at low and medium levels of political equality. Strikingly, instrumental variable estimates show that changes in electoral systems in political equal societies increases income inequality.
Keywords: D63; D72; C23; 330; Political equality; Income inequality; Proportional representation systems; Panel data